Through the Lens of a Large Instant-Messaging Network: Planetary-Scale Views on Behavior - Horvitz, Eric; Leskovec, Jure (2009)
Behavioral Studies at Planetary Scale Research questions: What are key structural properties of the communication graph? How do geographic relationships affect communication? How are communication patterns influenced by demographics (age, sex, language, country)?